Essays in international litigation for Lord Collins - Collins, Lawrence (Lawrence Antony); Harris, Jonathan, 1972-; McLachlan, Campbell (Oxford : Oxford University Press, 2022)
This collection is in honour of the remarkable career of Lord Collins. The book offers a set of unique insights into the conduct of cross-border litigation; the judicial role in international cases; the shape of English private international law; the conduct of international arbitration; and the interface with public international law.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 2, 2022).
Keywords: Conflict of laws; Actions and defenses; Law; Jurisprudence & general issues